Kajian signifikansi lanskap permukiman tradisional Pekon Hujung, Lampung Barat - Pratiwi, Rian Adetiya; Nabilah, Rizka; Wijayanti, Goldie Melinda (Jurnal Arsitektur Lansekap; Vol.7, No.1, April 2021DO - 10.24843/JAL.2021.v07.i01.p12, 2021)
Pekon Hujung is a traditional settlement located in Belalau District, West Lampung Regency and directly adjacent to South Oku, South Sumatra Province that describes the character of the Lampungnese people. The rapid pace of urban development and modernization can shift the cultural values that exist in a traditional settlement and its environment. One of the negative impacts that may arise is the loss of cultural importance in a traditional settlement area. An assessment of the importance or significance of a culture can be carried out as one way of determining an appropriate conservation strategy. This study was conducted to identify and to analyze the key characters that formed Pekon Hujung cultural landscape. The method used in this study is the Cultural Heritage Landscape Assessment (CHLA) which is used to assess the significance or importance of a landscape. The assessment resulted in important value score of 27, which was cllassified as high category of the landscape importance.  In general, Pekon Hujung has distinctive character, where the supporting elements, as well as the people still live and carry out the cultural values that have existed since long ago. The Pekon Hujung landscape is a culture that has important values and local wisdom which can still be applied in today's life.